Rapid determination of 13 organophosphorus flame retardants in milk by using modified quick, easy, cheap, effective, rugged, and safe technique, solid‐phase extraction, and HPLC‐MS/MS. Issue 11 (15th April 2021) - Chen, Xuelei; Li, Wei; Li, Jingguang; Fan, Sai; Shi, Zhixiong
Abstract: Organophosphorus flame retardants are a class of widely used plasticizers and flame retardants. In this study, an analytical methodology for the simultaneous determination of 13 organophosphorus flame retardants in milk was developed by using high‐performance liquid chromatography‐tandem mass spectrometry in combination with a modified quick, easy, cheap, effective, rugged, and safe technique and solid‐phase extraction. The experimental parameters of the sample purification procedure and high‐performance liquid chromatography‐tandem mass spectrometry were optimized. The developed method was validated in terms of linearity, limits of detection, recovery, and precision. The method showed a linear response in the 1–100 ng/mL concentration range and the limits of detection ranged from 0.001 to 0.3 ng/mL. The mean recoveries for most organophosphorus flame retardants were in the ranges of 75.0–115.8% (spiked at 2.5 ng/mL) and 76.7–124.8% (spiked at 25 ng/mL), with relative standard deviations of <13.09%. The developed methodology was successfully applied to the analysis of nine human milk samples and nine commercial cow milk samples. Eleven organophosphorus flame retardants were detected in the human milk samples, with median concentrations that ranged from lower than the limit of detection to 1.47 ng/mL, and only nine organophosphorus flame retardants were detected in cow milk samples, with median levels of <0.32 ng/mL.